2017
DOI: 10.1111/bju.13937
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative calculation of nephron volume loss on future of partial nephrectomy techniques; planning a strategic roadmap for improving functional preservation and securing oncological safety

Abstract: Preoperatively calculated RAIV significantly correlates with the amount of decline in PRF during long-term follow-up. The RAIV could lead our research to the level of prediction of the amount of PRF decline after PN and thus would be appropriate for assessing the technical advantages of emerging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Postoperative renal function has also been an important variable across RAPN outcome studies. Koon et al 24 found that their study population mean postoperative eGFR, when calculated with the MDRD equation, was 76.8 ml/min/1.73 m 2 . In a similar study, Veeratterapillay et al 25 found the mean 1-day postoperative eGFR to be 80.8 ± 27 ml/min/1.73 m 2 with a percentage change of −12.2 ± 17 from the preoperative eGFR.…”
Section: Discussionmentioning
confidence: 89%
“…Postoperative renal function has also been an important variable across RAPN outcome studies. Koon et al 24 found that their study population mean postoperative eGFR, when calculated with the MDRD equation, was 76.8 ml/min/1.73 m 2 . In a similar study, Veeratterapillay et al 25 found the mean 1-day postoperative eGFR to be 80.8 ± 27 ml/min/1.73 m 2 with a percentage change of −12.2 ± 17 from the preoperative eGFR.…”
Section: Discussionmentioning
confidence: 89%